2001
DOI: 10.1298/jjpta.4.19
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Influence by Ovariectomy and Calcium Diet on Bone Properties in Mice.

Abstract: This study was investigated the influence by ovariectomy (OVX) and calcium diet on bone properties in eighty-one female ICR strain mice with age of 5 weeks. The animals were randomly assigned to sham operation (SHAM), OVX, SHAM+low Ca intake (L.Ca) and OVX+L.Ca group. They were euthanized with lethal dose of pentobarbital sodium at day 50, 100 and 140 post-operatively. For determining the bone properties, both femur and tibial bones were excised from the hind limb, and removed off surrounding tissues. Thereaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This decreased density was consistent with other short-term OVX studies ( Fanti et al, 1998 ) and demonstrates that 17α-E2 is able to induce beneficial effects on diaphyseal bone. We also found that OVX resulted in greater femur length, which is commonly observed following OVX due to endogenous estrogens modulating osteoblast activity at the growth plate ( Minematsu et al, 2001 ). Importantly, 17α-E2 prevented increases in femur length, which suggests that 17α-E2 may be acting through ERα similarly to 17β-E2 to regulate growth plate closure ( Borjesson et al, 2012 ); a possibility that will need to be explored through future studies.…”
Section: Discussionsupporting
confidence: 51%
“…This decreased density was consistent with other short-term OVX studies ( Fanti et al, 1998 ) and demonstrates that 17α-E2 is able to induce beneficial effects on diaphyseal bone. We also found that OVX resulted in greater femur length, which is commonly observed following OVX due to endogenous estrogens modulating osteoblast activity at the growth plate ( Minematsu et al, 2001 ). Importantly, 17α-E2 prevented increases in femur length, which suggests that 17α-E2 may be acting through ERα similarly to 17β-E2 to regulate growth plate closure ( Borjesson et al, 2012 ); a possibility that will need to be explored through future studies.…”
Section: Discussionsupporting
confidence: 51%
“…[ 22 ] Another study found that the ash weight of the femur in mice was 58% of the dry weight. [ 23 ] DXA has the advantage of being able to simultaneously do both bone-related measurements and quantitative analysis of soft tissues, such as fat and lean. In addition, since X-rays used in DXA react with all substances and are attenuated, weight can be accurately calculated, and image analysis information on the shape or fat distribution of bones and organs is also provided through measurement images.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the dried and ash weights were 67% and 32% of the fresh weight of the right tibia and femur of hens [16]. Another study found that the ash weight of the femur in mice was 58% of the dry weight [17]. DXA has the advantage of being able to simultaneously do both bone-related measurements and quantitative analysis of soft tissues, such as fat and lean.…”
Section: Discussionmentioning
confidence: 99%